Compact E-Shaped Loop Patch Antenna for LoRaWAN Systems - Mengphan, Sureeporn; Kawdungta, Supakit; Pansomboon, Rassamitut (Engineering and Technology Horizons, 2023)
This research paper presents a compact E-shape loop patch antenna for internet of things (IoT) system based on LoRaWAN. The proposed patch antenna is designed in an E-shaped loop facing each other that it was to reduce the total size of the antenna. Both at once, this paper combined the technique of cutting slots on copper conductors and tuning stubs on the antenna structure which enhances the performance of the matching and expanding bandwidth. The size of the proposed antenna was 60.00 × 60.00 × 1.60 mm3. The comparison of simulated and measured results is good agreement. The measured results were found that the |S11| ≤ -10dB could cover the 917.00–933.50 MHz and a bandwidth of 16.5 MHz, that it was cover the LoRaWAN frequencies of Thailand. The proposed antenna has a gain of more than 1 dBi covering 920–925 MHz. The proposed antenna has an almost-omnidirectional radiation pattern and linear polarization. The suggested antenna was therefore appropriate for LoRaWAN systems.